Phytopharmacological And Phytochemical Properties Of Three Ficus Species-An Overview - BABY JOSEPH; S.JUSTIN RAJ (International Journal of Pharma and Bio Sciences, 2010)
Ficus plants are found throughout the world as moderate woody plants or trees. It has a vast traditional role in indigenious system of medicine like ayurveda, siddha, unani and homoeopathy. Ficus species, namely F. racemosa, , F. religiosa and F. benghalensis, are important ingredients in many Ayurvedic and traditional formulations. The barks ,leaves,fruits and latex are considered to be very effective in various treatments, such as diabetes, skin diseases, ulcers, dysentry, diarrohoea, stomachache, piles and as carminative ,astringent , anti inflammatory, antioxidant and anticancer agent. The present review is therefore, an effort to give a detailed survey of the literature on its phytochemical and pharmacological properties.